Pengembangan Aplikasi Web Manajemen Tugas Akademik Berbasis Model View Controller untuk Efisiensi Waktu Mahasiswa - Danendra Althaf Yuganfa; Reno Dwi Aderelyan; Daniel Aquaries Pratama; Arya Pradipta; Stephanus Abryan Agung Pratama; Cinantya Paramita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The need for an information system capable of managing academic activities and schedules in an integrated manner is increasing in higher education environments. This is due to students often facing difficulties in managing their time efficiently and effectively. This study aims to develop a web-based task management application that is not only functional but also has a proven quality of experience. With features such as task recording, calendar, and real-time notifications. The development method is carried out using the Waterfall approach, starting from gathering requirements to system design that includes three main components, namely: Use Case Diagram, Entity Relationship Diagram, and Activity Diagram. The Implementation stage is supported by the Model View Controller (MVC) architecture to ensure that the development process runs efficiently and organized. Then, at the testing stage, Black Box Testing and User Acceptance Test (UAT) with the Mean Opinion Score (MOS) method are carried out to validate the system. The results of the study show that all functions run according to design, with the highest level of user satisfaction in terms of functionality and performance. The contribution of this study lies in the effectiveness of cloud-based real-time notifications which are proven to be superior in increasing user awareness compared to conventional methods, as well as the availability of time management solutions that are verified to have a high level of user acceptance.